Developing Community Resilience through Grassroot Initiatives: Comparing Culturally Adapted Substance Use Prevention Programs Directed towards Indigenous Youth in Canada - Davies, Megan E. (HM Publisher, 2022)
Considering the growing prevalence of substance use amongst young people, prevention programs targeting children and adolescents are needed to protect against related cognitive, psychological, and behavioural issues. Preventative programs that have been adapted to Canadian Indigenous cultures in school and family settings are discussed. The first and second phase of the Life Skills Training (LST) program and the Maskwacis Life Skills Training (MLST) program are reviewed, as well as Bii-Zin-Da-De-Da (BZDDD; “Listening to One Another”) and a culturally sensitive smoking prevention program. Motivating factors, comorbid disorders, and at-risk personality types associated with substance use amongst Canadian children and adolescents, specifically Indigenous youth, are considered through the application of the biopsychosocial model. This paper aims to describe the requital efforts being made in Canada towards Indigenous communities, to compare substance use prevention programs targeting Indigenous children and adolescents, and to provide suggestions for future research on preventative interventions directed towards substance use within minority groups.